"The People's Judge": Jacob Panken, Yiddish Socialism, and American Law. Issue 1 (28th January 2019) - Tevis, Britt P
Abstract: This article explores the career of Jacob Panken, the first judge elected on a Socialist Party ticket in the United States. Situating Panken in an early twentieth-century Jewish immigrant milieu and analyzing some of the cases over which he presided, it shows how he employed legal realism to weave Yiddish socialism, a political philosophy espoused by turn-of-the-century Eastern European Jews in New York City, into his judicial decisions. Illuminating Panken's unique place in the American judiciary, it contributes to scholarship on American socialism, twentieth-century American Jewish lawyers, and local legal histories.